Summoning the spirit [videorecording (DVD)] - Garcia, Jon; Valdes, Krystal Millie; Reyes, Ernesto (Actor); Tayeh, Jesse (Darkstar Pictures, 2023)
Carla and Dean decide to escape the city, only to find themselves on the remote land of a strange cult claiming a connection to the flesh-eating bigfoot. Now they must save themselves and uncover the terrifying truth of the cult's prophecy.